2006
DOI: 10.1038/sj.eye.6702518
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal triamcinolone acetonide for macular oedema owing to retinal vein occlusion

Abstract: Purpose To assess the long-term safety and efficacy of intravitreal triamcinolone acetonide injection in the management of macular oedema caused by central, hemi-, and branch retinal vein occlusion (CRVO, HRVO, or BRVO). Methods This prospective, interventional case series included 13 patients (13 eyes) with retinal vein occlusion and macular oedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 25 publications
2
23
1
2
Order By: Relevance
“…In addition to that Özkiris et al [4] reported successful functional and structural improvement in BRVO with ineffective previous laser photocoagulation. These promising results of triamcinolone in BRVO-associated macular edema and in other edematous retinal diseases [17] has led to trials testing triamcinolone as a general approach for BRVO macular edema [5,7,13,[17][18][19][20][21]. Unfortunately, the design of these studies was relatively heterogenous concerning the selection of cases, history of disease, used dosage of triamcinolone, management of re-injections, and follow-up periods.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition to that Özkiris et al [4] reported successful functional and structural improvement in BRVO with ineffective previous laser photocoagulation. These promising results of triamcinolone in BRVO-associated macular edema and in other edematous retinal diseases [17] has led to trials testing triamcinolone as a general approach for BRVO macular edema [5,7,13,[17][18][19][20][21]. Unfortunately, the design of these studies was relatively heterogenous concerning the selection of cases, history of disease, used dosage of triamcinolone, management of re-injections, and follow-up periods.…”
Section: Discussionmentioning
confidence: 93%
“…In two studies [4,21], applying 8 mg of triamcinolone, visual improvement persisted 6 months without reinjection. The conclusion from the majority of reports is that single injections of triamcinolone are not always sufficient for regaining maximal possible function [18] nor do they create a permanent functional or structural improvement [6,7,18,20,22,23]. Only a transient elevation of visual acuity was observed at 1 month after a single injection of 4 mg [6] or even 20-25 mg [7], which did not persist until the next follow-up examination at 2 months [7] or 3 months [6] respectively.…”
Section: Discussionmentioning
confidence: 97%
“…91,92 Focal laser photocoagulation is useful in avoiding visual loss in patients with macular edema from BRVO, although this treatment does not appear to benefit macular edema associated with central RVO. 91,92 Newer therapeutic options for macular edema in the form of intravitreal triamcinolone [91][92][93] and anti-vascular endothelial growth factor agents 91,92,94 currently seem to be at the forefront, and their efficacy and safety is being validated by randomized clinical trials. Although there is no evidence that lowering of blood pressure would reduce the risk of complications associated with RVO, physicians should be more vigilant with the patients' treatment of hypertension after the occurrence of an RVO.…”
Section: How Does Hypertension Affect Your Eyes? M Bhargava Et Almentioning
confidence: 99%
“…Triamcinolone acetonide has been shown to have antiedematous and antiangiogenic properties. Based on these characteristics, several authors have published case series with administered dosages varying from 4 to 25 mg [88,89,90,91,92]. The results available in the literature are difficult to be interpreted owing to several features, including the retrospective nature of most studies, the limited number of patients, the short follow-ups, the different durations of ME, and sometimes the lack of differentiation between ischemic and nonischemic BRVO.…”
Section: Treatmentmentioning
confidence: 99%
“…First of all, the intravitreal injection of triamcinolone acetonide (IVTA) is effective in improving VA and reducing ME, but the efficacy is greatest following the first injection and tends to reduce after repeated injections, with a possible tachyphylactic effect [91]. There is no definite correlation of VA with macular thickness, duration of BRVO, or baseline VA. Second, it is not yet clear if repeated IVTA injections can lead to a sustained effect [91, 92]. Third, even though IVTA is able to reduce macular thickness, it is probably not beneficial for the ischemic form of BRVO [89, 90].…”
Section: Treatmentmentioning
confidence: 99%